Immediate Postpartum Intrauterine Device Insertion, Implant Insertion and Sterilization, U.S., 2008-2013 [33B]. (May 2017) - Moniz, Michelle; Chang, Tammy; Heisler, Michele; Admon, Lindsay; Davis, Matthew; Dalton, Vanessa
Abstract : INTRODUCTION: Our objective was to measure trends in immediate postpartum intrauterine device (IUD) insertion, contraceptive implant insertion, and tubal sterilization. METHODS: Among all delivery hospitalizations in the 2008-2013 National Inpatient Sample, we identified those with codes for tubal sterilization, IUD insertion, or contraceptive implant insertion. We used multivariate and multinomial logistic regression to examine associations between these outcomes and maternal and hospital characteristics over time. RESULTS: While the rate of sterilization remained similar over time, the rate of IUD/implant insertion increased over the study period (1.86 per 10, 000 deliveries in 2008-09; 13.5 per 10, 000 deliveries in 2012-13). Compared with receiving neither IUD/implant nor sterilization and adjusting for year and sociodemographic factors, IUD/implant insertion was more likely among women with medical comorbidity (adjusted odds ratio [aOR]=1.92; 95% confidence interval 1.72-2.13), with non-private insurance (aOR=5.23; 3.82-7.15), and delivering at teaching hospitals (aOR=19.8; 9.41-41.5). Sterilization was more likely among women with medical comorbidity (aOR=1.17; 1.14-1.20) and non-private insurance (aOR=2.20; 2.10-2.30), and less likely among women receiving care at urban versus rural facilities (aOR=0.59, 0.55-0.63). Comparing only women receiving IUD/implant insertion or sterilization, IUD/implant insertion was more likely among women with non-private insurance (aOR=1.9; 1.38-2.63), delivering at urban (aOR=2.18; 1.01-4.70) or teaching (aOR=17.6; 8.50-36.5) hospitals, and delivering later in the study period (aOR=4.51 in 2010-11; aOR=8.26 in 2012-13, compared to 2008-09). CONCLUSION: During delivery hospitalizations in the US from 2008-2013, the IUD/implant insertion rate increased by an order of magnitude. Immediate postpartum IUD/implant insertion is associated with medical comorbidities, non-private insurance status, and urban/teaching hospital status.